Semiotics the basics - Chandler, Daniel (Routledge, 2017)
"This third edition of the bestselling textbook has been fully revised, continuing to provide a concise introduction to the key concepts of semiotics in accessible and jargon-free language. Demystifying what is a complex, highly interdisciplinary field, key questions covered include: What are signs and codes? What can semiotics teach us about representation and reality? What tools does it offer for analysing texts and cultural practices? With further examples and images and new end of chapter resources, this must-have resource is both the ideal introductory text and an essential reference guide for students at all levels of language and communication, media and cultural studies."--Provided by publisher.